Utilizing Primary and Secondary Research to identify the target Audience and Drive High-Performance Campaigns for the Pillow Category - Abhishek Shetty (North American Journal of Engineering Research, 2021)
This paper explores the utilization of primary and secondary research to gain a comprehensive understanding of the target audience for a pillow brand. By analyzing customers' sleep problems and pillow preferences, this study aims to develop targeted high-performance marketing campaigns to drive return on investment (ROI). The research includes the development of a comprehensive survey, data collection, and statistical analysis to identify key factors influencing consumer purchase decisions. The findings inform a strategic digital marketing plan to effectively reach and engage potential customers.